The knife of dawn chamber opera for baritone and small ensemble : 2016 - Kendall, Hannah; Carter, Martin 1927-1997 (Ricordi, 2022)
"The knife of dawn explores the life and mind of Guyanese poet and political activist Martin Carter as he boldly fights for his country's independence"